Contributions of Madrasah Diniyah Takmiliyah Awaliyah to Advancing Qur'anic Literacy - Helena, Yanti; Nahar, Syamsu; Nasution, Wahyudin Nur (Sekolah Tinggi Agam Islam Sumatera Medan, 2024)
Al-Qur'an literacy is a significant challenge in Indonesia, where most students have low reading and comprehension skills. This phenomenon is exacerbated by changes in learning culture, such as children's preference for gadgets and digital entertainment, which reduces the time available for reading the Al-Qur'an. This study aims to analyze the contribution of Madrasah Diniyah Takmiliyah Awaliyah as a driver of Quran literacy in Padangsidimpuan City, as well as to explore learning strategies, supporting factors, and obstacles to its implementation. The method used is multisite qualitative, with data collection through participatory observation, interviews, and documentation in two madrasas. The results show that the Qur'an literacy program at Madrasah Diniyah Takmiliyah Awaliyah, including tahsin, tahfiz, and tilawah competitions, is effective in improving reading and comprehension skills, as well as fostering a love for and internalization of the values of the Qur'an. The success of the program depends on teacher competence, parental involvement, and a conducive learning environment. The implications of this study confirm the strategic role of Madrasah Diniyah Takmiliyah Awaliyah as a non-formal institution that strengthens Al-Qur'an literacy, shapes religious character, and prepares a generation of Muslims with noble character and Qur'anic competence.